Thymic Stromal Lymphopoietin Is Critical for Regulation of Proinflammatory Cytokine Response and Resistance to Experimental Trypanosoma congolense Infection - Onyilagha, Chukwunonso; Singh, Rani; Gounni, Abdelilah Soussi; Uzonna, Jude Ezeh (Frontiers in Immunology, 2017)
African trypanosomiasis (sleeping sickness) poses serious threat to human and animal health in Sub-Saharan Africa. Because there is currently no vaccine for preventing this disease and available drugs are not safe, understanding the mechanisms that regulate resistance and/or susceptibility to the disease could reveal novel targets for effective disease therapy and prevention. Thymic stromal lymphopoietin (TSLP) plays a critical role in driving Th2 immune response. Although susceptibility to experimental T. congolense infection in mice is associated with excessive proinflammatory responses due in part to impaired Th2 response, the role of TSLP in resistance to African trypanosomiasis has not been well studied. Here, we investigated whether TSLP is critical for maintaining Th2 environment necessary for survival of T. congolense-infected mice. We observed an increased TSLP level in mice after infection with T. congolense, suggesting a role for this cytokine in resistance to the infection. Indeed, infected TSLPR-/- mice were more susceptible to T. congolense infection and died significantly earlier than their wild type (WT) controls. Interestingly, serum levels of IFN- and TNF- and the frequency of IFN- and TNF-- producing CD4+ T cells in the spleens and liver were significantly higher in infected TSLPR-/- mice than in the WT control mice. Susceptibility was also associated with excessive M1 macrophage activation. Treatment of TSLPR-/- mice with anti-IFN- mAb during infection abolished their enhanced susceptibility to T. congolense infection. Collectively, our study shows that TSLP plays a critical role in resistance to Trypanosoma congolense infection by dampening the production of proinflammatory cytokines and its associated M1 macrophage activation.